2022
DOI: 10.1101/2022.01.11.22268981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid and Accurate Identification of SARS-CoV-2 Omicron Variants Using Droplet Digital PCR (RT-ddPCR)

Abstract: Background Mutations in the receptor binding domain of the SARS-CoV-2 Spike protein are associated with increased transmission or substantial reductions in vaccine efficacy, including in the recently described Omicron variant. The changing frequencies of these mutations combined with their differing susceptibility to available therapies have posed significant problems for clinicians and public health professionals. Objective To develop an assay capable of rapidly and accurately identifying variants including O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Also, viral mutations pose a potential challenge to nucleic acid testing methods, leading to the occurrence of FNRs ( 140 ). For example, some assays have reported S gene dropout or S gene target failure (SGTF) in RT-qPCR and RT-dPCR assays targeting SARS-CoV-2’s S gene due to mutations caused by the Alpha and Omicron variants ( 139 , 141 144 ). Although specific mutations might compromise the sensitivity of the assays, it has been suggested that such assays may be used as a surrogate marker for the variants pending confirmation by sequencing ( 139 , 143 , 145 ).…”
Section: Synoptic Overview Of Sars-cov-2 Rt-dpcr Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, viral mutations pose a potential challenge to nucleic acid testing methods, leading to the occurrence of FNRs ( 140 ). For example, some assays have reported S gene dropout or S gene target failure (SGTF) in RT-qPCR and RT-dPCR assays targeting SARS-CoV-2’s S gene due to mutations caused by the Alpha and Omicron variants ( 139 , 141 144 ). Although specific mutations might compromise the sensitivity of the assays, it has been suggested that such assays may be used as a surrogate marker for the variants pending confirmation by sequencing ( 139 , 143 , 145 ).…”
Section: Synoptic Overview Of Sars-cov-2 Rt-dpcr Applicationsmentioning
confidence: 99%
“…Building on the same assay ( 144 ), Mills et al sought to further develop the assay to be capable of identifying key mutations in the spike region of SARS-CoV-2 and applied it to rapidly and accurately detect the recently emerged Omicron variant in clinical specimens ( 142 ). In this study, 390 clinical specimens were first screened using the assay, and the results matched 99% with whole-genome sequencing (WGS) results.…”
Section: Synoptic Overview Of Sars-cov-2 Rt-dpcr Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…No clinical information was available for HMIX1 and HMIX2. Samples 5BG and 8LH were also tested by a separate PCR assay to detect S-gene target failure (ThermoFisher TaqPath assay), and a droplet digital (RT-dd)PCR assay targeting four different loci in the spike gene (417K, 452L, 484E, 501N) ( 3 , 4 ) (Table S1, Fig. 1B ).…”
Section: Lettermentioning
confidence: 99%